Investigation On Combustion Characteristics Of Municipal Solid Waste From Penang State Malaysia. - Siang, Piao Chai; Zakaria, Ridzuan (2006)
Landfill, a common technique used for solid waste disposal in Malaysia, currently cannot effectively manage it due to the increasing volume of municipal solid waste (MSW) generated daily in this country.